Early Pain Outcome of Open Lumbar Discectomy Versus Endoscopic Lumbar Discectomy - Muhammad Usman Anwar, Talha Abbas, Nabeel Choudhary, Rida Zahid, Adeel-Ur-Rehman, Mohammad Faheem Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: A prolapsed intervertebral disc is one of the principal causes of low back pain in the adult population. It is most common in the fourth and fifth decades of life and occurs in lumbosacral and cervical regions. Objectives: This study was conducted to compare mean postoperative pain after endoscopic discectomy and open discectomy for the surgical treatment of lumbar disc herniation by utilization VAS. Methodology: This was a randomized controlled trial conducted in the department of Neurosurgery Sir Ganga Ram Hospital Lahore. The study was conducted from 15 January 2020 to 15 August 2021. Inclusion and exclusion criteria were defined and a total of 100 patients were recruited for the study. The patients were randomized into two groups. VAS scores for both the groups were recorded pre-operatively and were compared with post-operative VAS scores. One group underwent open discectomy, whereas, others underwent minimally invasive endoscopic lumbar discectomy. Results: A total of 100 subjects with a mean age of 41.32 ± 11.88 years were recruited for this study. Males accounted for 67% of the subjects whereas females accounted for 33% of the subjects. L4-L5 disc prolapse accounted for 71% of the cases. The average duration of complaint was 72.17 ± 27 days. VAS Score improvement at 24 hours, 01 week and 01 month was compared among the 2 groups and a statistically significant difference was found among endoscopic and open discectomy with a p value of <0.005. Conclusion: Our results have shown that minimally invasive endoscopic lumbar discectomy is superior to conventional open discectomy in terms of pain outcomes. In trained hands, endoscopic lumbar discectomy is a better treatment modality as compared to conventional open discectomy if patient is carefully selected. Keywords: Sciatica, Intervertebral Disc Displacement, Discectomy, Percutaneous, Intervertebral Disc Degeneration